PENGARUH PENERIMAAN PIUTANG TERHADAP SERVICE CHARGE KARYAWAN THE ALTS HOTEL PALEMBANG - Rusmida Hutabarat; Ernawati . (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
ABSTRACK               The purpose of this study was to determine  the Effect of Acceptance of Receivables Against Employee Charge Service at The Alts Hotel Palembang which is located at Jalan Rajawali no 8 Palembang. The purpose of this study is to know and analyze how much influence receivables receivables to service charge employees The Alts Hotel Palembang. In this study using primary and secondary data with the method of analysis used is quantitative methods and analysis techniques used are simple linear regression method, correlation analysis, hypothesis test (t) and coefficient of determination               The results showed that there is a positive influence between receipt of receivables to employee service charge The Alts Hotel Palembang because the calculation of t count value of 2.960> t table of 2.22814 and at significant 0.014 <0.05 then H0 rejected and H1 accepted which means receivables Affect the service charge at the level of α = 0.05 and can be indicated by the coefficient of determination of 0.467 or 46.7% which means that the service charge is affected by the receipt of receivables 46.7% while the remaining 53.3% influenced by other factors. The Alts Hotel Palembang still uses revenue recognition based on cash basis. Keywords : receivables receipt and service charge